Turkey : Selected Issues. (IMF Staff Country Reports; Country Report, 2012)
This Selected Issues paper on Turkey discusses the new monetary framework adopted by the Central Bank of Republic of Turkey (CBRT). Instead of relying on one interest rate as inflation-targeting, the CBRT resorted to raising it as inflation pressures intensify and lowering it as they abate. The first version of the framework does not seem to have achieved significant reduction in external and internal imbalances, but the second version of the framework has witnessed an unwinding of imbalances.